Growing up in the deep-sea protected development in deep-sea invertebrates: A case study in the southwestern Atlantic Ocean - Teso, Silvia Valeria (2020)
Marine invertebrates display a range of reproductive strategies, from external fertilization to several methods to protect the young. Both brooding or protected development of benthic species and direct development species (when juveniles born in a smaller version of its adult form) involves reducing the time that the larvae and/or juveniles spend in the plankton. The different forms of juvenile protection are often associated with the taxonomic group, although certain groups are much diversified in terms of their reproductive modes. However, the area where the species live also seems to play a key role. Several authors have indicated the unusual proportion of brooding species in the Southern Ocean, in particular in the southwestern Atlantic, including its adjacent deep-sea. The knowledge about the reproductive characteristics of most of the fauna in this area remains unknown. Proof of this are the great number of studies carried out in recent years, describing the reproductive features of several species (many also new), with some of them having many peculiarities about their biology.